MQTT-VET: Exploring MQTT Protocol Vulnerabilities - Freitas, Ana Vitoria; Araújo Júnior, Silvio Romero de; Silva, Hebert (Anais Estendidos do Latin-American Symposium on Dependable and Secure Computing (LADC), 2024)
The Message Queuing Telemetry Transport (MQTT) protocol is essential for IoT communications, enabling lightweight device messaging. However, its widespread use increases security vulnerabilities. This paper introduces the MQTT Vulnerability Exploration Testbed (MQTT-VET), a container-based environment to analyze and exploit MQTT weaknesses in IoT setups. It simulates real-world scenarios to identify critical security flaws in MQTT implementations, offering practical security tools and guidelines for developers and network administrators. The preliminary results suggest that container-based testbeds can improve IoT security across various sectors.